2012
DOI: 10.1097/qad.0b013e328355fe8f
|View full text |Cite
|
Sign up to set email alerts
|

Abacavir induces loading of novel self-peptides into HLA-B*57

Abstract: Background Abacavir drug hypersensitivity in HIV-treated patients is associated with HLA-B*57:01 expression. To understand the immunochemistry of abacavir drug reactions, we investigated the effects of abacavir on HLA-B*57:01 epitope-binding in vitro and the quality and quantity of self-peptides presented by HLA-B*57:01 from abacavir-treated cells. Design and methods An HLA-B*57:01-specific epitope-binding assay was developed to test for effects of abacavir, didanosine or flucloxacillin on self-peptide bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(79 citation statements)
references
References 23 publications
(27 reference statements)
1
76
0
Order By: Relevance
“…Neither carbamazepine nor abacavir hypersensitivity peptides eluted from purified HLA molecules of drug-pulsed APC carried a covalently bound drug [27,28,29,30]. Indeed, a highly selective HLA allele association argues against the involvement of a hapten-driven T cell stimulation.…”
Section: P-i Hla and P-i Tcrmentioning
confidence: 99%
See 3 more Smart Citations
“…Neither carbamazepine nor abacavir hypersensitivity peptides eluted from purified HLA molecules of drug-pulsed APC carried a covalently bound drug [27,28,29,30]. Indeed, a highly selective HLA allele association argues against the involvement of a hapten-driven T cell stimulation.…”
Section: P-i Hla and P-i Tcrmentioning
confidence: 99%
“…A breakthrough in understanding the link between DHR and HLA association was the crystallographic structure of the HLA-B*57:01 molecule with bound abacavir [29,30]. It showed that the drug binds below the peptide presented by the HLA-B*57:01 molecule, away from the site of peptide-TCR interaction [28,29].…”
Section: P-i Hla and P-i Tcrmentioning
confidence: 99%
See 2 more Smart Citations
“…• Many severe DHR were linked to the presence of a certain HLA allele due to direct drug binding to a critical region of the HLA protein and thus represent a typical “p-i HLA”-type reaction [25,27,28,29,32,33,34,35,36]. …”
Section: Sjs/ten and Dress Are P-i Reactionsmentioning
confidence: 99%